Regulation oriented architectur (ROA) to improve public management in Huánuco Region Government - Bravo-Vecorena, Aland (2019)
The Focus on this research was to develop an improved version of the Viable Model System (VMS) [2], through the Regulation Oriented Architecture (ROA) technique [1], in Huánuco Region Government (HRG) to improve its Public Management not only on their concentrated organic units but also on their des concentrated organic units (read the last as sectorial regional directions), given as a result an strategic guide tool for diagnosis of systemic organizational situation on Huánuco region in the coming decades, weighing urgent projects, meeting the important and strategic projects.